The Effect of the Application of the Learning Model 6 Step Teaching Factory (Tf-6m) and Achievements Learning Entrepreneurship on Interest Entrepreneurs for Vocational Students - Edy Siswanto; Samsudi Samsudi; Eko Supraptono; Yeri Sutopo (Universitas Negeri Semarang, 2021)
Teaching Factory 6M Learning Model is an integrated learning model. Entrepreneurship Subjects (Mapel) that are refined into Creative Products and Entrepreneurship (PKKWU) are a learning process for inculcating entrepreneurial values ​​through habituation and maintenance of behavior and attitudes. Through the Teaching Factory Learning Model supported by PKKWU learning, students are expected to have an interest in entrepreneurship. The application of the Teaching Factory Learning Model aims to shape student competencies through a unified school environment based on industry and supported by the implementation of PKKWU learning in the formation of an entrepreneurial mentality. This article examines the effect of applying the Teaching Factory 6M Learning Model and Learning Achievement of Creative and Entrepreneurial Products on Entrepreneurial Interests in students of SMK Negeri 4 Kendal. The research method used in this research is descriptive and verification method.